Characteristics of 637 melanomas documented by 27 general practitioners on the Skin Cancer Audit Research Database. (23rd August 2021) - Jimenez Balcells, Clara; Hay, Jeremy; Keir, Jeff; Rosendahl, Nikita; Coetzer‐Botha, Martelle; Wilson, Tobias; Clark, Simon; Baade, Astrid; Becker, Cath; Bookallil, Luke; Clifopoulos, Chris; Dicker, Tony; et al.
ABSTRACT: Background and Objective: Most melanomas (including melanomas in situ), in Australasia, are treated by general practitioners (GPs). Previously undescribed, the characteristics of a series of melanomas treated by multiple GPs are examined. Patients and Methods: Six hundred and thirty‐seven melanomas treated by 27 Australasian GPs during 2013 and documented on the Skin Cancer Audit Research Database (SCARD) were analysed by anatomical site, subtype, Breslow thickness, diameter, associated naevi and linked adverse outcomes. Results: Most melanomas (59.7%) were on males, mean age at diagnosis being 62.7 years (range 18–96). Most (65.0%) were in situ, with a high incidence of lentiginous melanoma (LM) (38.8%) and 32% were naevus associated. Most LM (86.4%) were in situ, compared to 55% of superficial spreading melanoma (SSM) ( P  < 0.0001). There was male predominance on the head, neck and trunk and female predominance on extremities. There was no significant association between Breslow thickness and diameter, with small melanomas as likely to be thick as large melanomas, and melanomas ≤3 mm diameter, on average, more likely to be invasive than larger melanomas. There was a positive correlation between age and both melanoma diameter and Breslow thickness. Seven cases progressed to melanoma‐specific death: Five nodular melanoma (NM) and two SSM, one of which was thin (Breslow thickness 0.5 mm). Conclusions: A large series of melanomas treated by Australasian GPs were predominantly in situ, with a high proportion of LM subtype. With implications for GP training, NM linked to death was over‐represented and there was a novel finding that older patients had larger diameter melanomas.